Voices of emergency: Imagined climate futures and forms of collective action - Clot-Garrell, Anna (Current Sociology, 2024)
Sociological debates on the mobilising force of imagined futures are particularly relevant in our present context of climate emergency, where the claim-making of a 'threatened future' has come to the fore in civic mobilisations worldwide. This article addresses these debates by empirically examining how adverse views of the future underpinning present thematisations of climate change as an emergency shape collective action. Based upon qualitative research conducted in Barcelona on new climate movements, I analyse the content and form of two imagined futures ('catastrophe' and 'collapse') that emerge from the ways in which participants of Extinction Rebellion and Fridays for Future engage with the future and climate. This analysis shows how these imagined futures are reflected in individual imaginations and processed by these movements, infusing different forms of agency and impacting trajectories of action in the present. This empirically grounded focus on imagined climate futures reveals that not only are cognitions of climate risks crucial, but so are the emotions that these produce in configuring collective action. Likewise, this study highlights how even disastrous imagined climate futures include utopian impulses for sustainable futures as both a driver and result of collective action.
Keywords: Collective Action; Emotions; Environmental Movement; Imagined Futures; Climate Change